Mannose-decorated ginsenoside Rb1 albumin nanoparticles for targeted anti-inflammatory therapy - Fu, Zhihui; Wang, Xiaohui; Lu, Xuan; Yang, Ying; Zhao, Lingling; Zhou, Lin; Wang, Kaikai; Fu, Hanlin (Frontiers in Bioengineering and Biotechnology, 2022)
Ginsenoside Rb1 is a potential anti-inflammatory natural molecule, but its therapeutic efficacy was tremendously hampered by the low solubility and non-targeted delivery. In this study, we innovatively developed a mannose (Man) modified albumin (BSA) carrier (Man-BSA) to overcome the above dilemmas of Rb1. The constructed Man-BSA@Rb1 NPs could improve the solubility and increase cellular uptake of Rb1, finally leading to the enhanced anti-inflammatory effects. The robust therapeutics of Man-BSA@Rb1 NPs were measured in terms of nitrite, tumor necrosis factor-α (TNF-α), Interleukin-6 (IL-6) levels, which might be achieved by potently inhibiting nuclear factor-κB (NF-κB) and mitogen-activated protein kinase (MAPK) signaling pathways in lipopolysaccharide (LPS)-induced Raw264.7 cells. Moreover, the therapeutic efficacy of Man-BSA@Rb1 NPs was further confirmed in d-Gal/LPS induced liver injury model. The results indicated that Man-BSA may offer a promising system to improve the anti-inflammatory therapy of Rb1.